Exploring strategies within the informal economy: three essays on illegal online pharmacies. - Almutawa, Musab (IE University, 2021)
The informal economy is often understudied, and as a result we lack a conceptual understanding about how firms compete and strategize in the illegal side of the economy. In this dissertation, I seek to redress this by looking at strategies that illegal online pharmacies and their stakeholders use to help elucidate general management theories, through three empirical essays. In the first essay I look at how audiences respond to the use of multiple impression management efforts, and show that at a certain point adding efforts may be detrimental because suspicion might be triggered. This emphasizes the importance of exploring cogitation when looking at impression management. In the second essay I provide a novel rationale for why some certifications could be detrimental to the firm, by looking at violations of audience expectations. I demonstrate that if audiences believe problems to be salient in a firm, then certifications are seen as a way to showcase that those problems are being addressed, resulting in a positive expectancy violation and improved trust outcomes. If, however, the problem is not seen as salient, then certifications provide information that the problem is more salient than originally expected, giving rise to a negative expectancy violation and worse trust outcomes. In the third essay I build a more nuanced model about who regulators target. I argue that regulators will be less likely to target violators with strong competitive advantages and hard-to-build resources/capabilities, because they are more likely to ignore them given how much they would lose, and are therefore relatively costlier to purse. My dissertation contributes to a number of management theories including impression management, certification, expectancy violations, and regulatory enforcement theories.
Explorando estrategias dentro de la economía informal: tres ensayos sobre las farmacias ilegales online .
La economía informal suele estar poco estudiada, por lo que carecemos de una comprensión conceptual sobre cómo compiten y elaboran estrategias las empresas en la parte ilegal de la economía. En esta tesis, trato de corregir esta situación examinando las estrategias que utilizan las farmacias ilegales online que atienden al mercado estadounidense, así como sus grupos de interés, para ayudar a dilucidar las teorías generales de gestión a través de tres ensayos empíricos. En el primer ensayo examino cómo responde el público al uso de múltiples esfuerzos de gestión de la impresión, y muestro que en un determinado momento añadir esfuerzos puede ser perjudicial porque puede surgir la sospecha. Esto subraya la importancia de explorar la reflexión cuando se estudia la gestión de la impresión. En el segundo ensayo ofrezco una novedosa justificación de por qué algunas certificaciones pueden ser perjudiciales para la empresa, examinando los incumplimientos de las expectativas del público. Demuestro que si el público cree que los problemas son importantes en una empresa, las certificaciones se ven como una forma de mostrar que esos problemas se están abordando, lo que da lugar a un incumplimiento positivo de las expectativas y a una mejora de los resultados de la confianza. Si, por el contrario, el problema no se considera significativo, las certificaciones informan de que el problema es más importante de lo que se esperaba en un principio, lo que da lugar a un incumplimiento negativo de las expectativas y a peores resultados de confianza. En el tercer ensayo construyo un modelo más matizado sobre a quién se dirigen los organismos de control. Sostengo que es menos probable que los organismos de control se dirijan a los infractores con fuertes ventajas competitivas y recursos/capacidades difíciles de crear, porque es más probable que los ignoren dado lo mucho que perderían, y por lo tanto son relativamente más costosos de perseguir. Mi tesis contribuye a una serie de teorías de gestión, como la gestión de las impresiones, la certificación, los incumplimientos de las expectativas y las teorías de cumplimiento de las leyes.
Keywords: Informal economy; Organizational strategy; Impression management; Regulatory enforcement